Serum zinc concentrations and depression in persons with Human Immunodeficiency Virus infection: The positive living with HIV (POLH) study. (30th July 2016) - Poudel-Tandukar, Kalpana; Jacelon, Cynthia S.; Bertone-Johnson, Elizabeth R.; Palmer, Paula H.; Poudel, Krishna C.
Abstract: Low levels of serum zinc concentrations and depression are common in persons infected with Human Immunodeficiency Virus (HIV). Low levels of serum zinc concentrations may increase risk of depression in general population. However, research on the role of zinc in depression among HIV- infected person is limited. We assessed the association between serum zinc concentrations and depression in HIV-infected persons. A cross-sectional survey was conducted among 311 HIV-positive people (177 men and 134 women) aged 18-60 years residing in Kathmandu, Nepal. The atomic absorption method was used to measure serum zinc concentrations and the Beck Depression Inventory (BDI)-Ia method was used to measure depression, with cut off score 20 or higher consistent with clinically significant depression. Relationships were assessed using multiple linear and logistic regression analyses. Serum zinc concentrations were significantly inversely associated with depression in all participants and in men but not in women. Participants with the highest tertile of serum zinc concentrations had a significantly decreased risk of depression in men but not in women. Serum zinc concentrations were inversely associated with depressive symptoms scores in HIV-infected men. Further prospective studies are needed to confirm the role of zinc in depression among persons infected with HIV. Highlights: Zinc deficiency and depression are common in HIV- infected persons. Zinc deficiency was associated with increased risk of depression in general population. We examined the association between zinc and depression in HIV- infected persons. Higher zinc concentrations was associated with decreased risk of depression in HIV- infected persons.